Analisis Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Kapitalisasi Pasar Sebagai Variabel Moderasi (Studi Pada Perusahaan yang Tercatat di Indeks JII70 Periode 2017-2019) - Haris Setiawan, Achmad; Nanang Choiruddin, Muhammad (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Abstract: This study aims to find the effect of profitability and dividend policy on firm value with market capitalization as a moderating variable for companies listed on the JII70 Index for the 2017-2019 period. This research is a quantitative research type with a sample population of 104 companies listed in the JII70 Index listed on the Indonesia Stock Exchange in the 2017-2019 period. Furthermore, purposive sampling was carried out to obtain 34 companies that fit the criteria. The results obtained in this study indicate that there is a significant influence between profitability and market capitalization on firm value, only dividend policy has no significant effect on firm value. Meanwhile, the MRA test shows that market capitalization is not able to partially moderate the relationship between profitability and dividend policy on firm value.